2014
DOI: 10.1161/atvbaha.114.302523
|View full text |Cite
|
Sign up to set email alerts
|

Calcific Aortic Valve Disease

Abstract: Calcific Aortic Valve Disease (CAVD) is increasingly prevalent worldwide with significant morbidity and mortality. Therapeutic options beyond surgical valve replacement are currently limited. In 2011, the National Heart Lung and Blood Institute assembled a working group on aortic stenosis. This group identified CAVD as an actively regulated disease process in need of further study. As a result, the Alliance of Investigators on CAVD was formed to coordinate and promote CAVD research, with the goals of identifyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
130
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 284 publications
(132 citation statements)
references
References 69 publications
(76 reference statements)
0
130
0
2
Order By: Relevance
“…However, emerging evidence has indicated that this condition is mediated by the interplay of complex biological processes that include the following: inflammation, cell apoptosis, lipids deposition, renin-angiotensin system activation, remodeling of the extracellular matrix, and bone formation [411]. However, the underlying mechanisms that regulate this process remain largely unknown [12, 13]. …”
Section: Introductionmentioning
confidence: 99%
“…However, emerging evidence has indicated that this condition is mediated by the interplay of complex biological processes that include the following: inflammation, cell apoptosis, lipids deposition, renin-angiotensin system activation, remodeling of the extracellular matrix, and bone formation [411]. However, the underlying mechanisms that regulate this process remain largely unknown [12, 13]. …”
Section: Introductionmentioning
confidence: 99%
“…Degenerative AV stenosis has become the most common type of VHD in developed countries [10], and it often involves valvular calcification. Whether the AV is especially susceptible to calcification is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…However, considerable evidence has now accumulated from molecular studies supporting a cell-mediated active malady involving risk factors and histopathophysiological features (endothelial cell and macrophage activation, proteolytic activity, and osteogenesis in inflamed valves with similarities to skeletal bone formation) that characterize atherosclerosis [6, 8, 9]. It was probably Leonardo da Vinci (1452–1519) [10] who first recognized atherosclerotic macroscopic changes; when he illustrated arterial atherosclerotic lesions in an elderly man at autopsy, he attributed the thickening of the vessel wall to “excessive nourishment” from the blood [11].…”
Section: Molecular Genomic and Histopathologic Aspects Of Cavdmentioning
confidence: 99%